Amelioration of amyloid β-induced retinal inflammatory responses by a LXR agonist TO901317 is associated with inhibition of the NF-κB signaling and NLRP3 inflammasome. (30th September 2017) - Lei, Chunyan; Lin, Ru; Wang, Jiaming; Tao, Lifei; Fu, Xinyu; Qiu, Yiguo; Lei, Bo
Highlights: Aβ1-40 lead to over production of inflammatory cytokines, microglial response and retinal dysfunction. Activation of LXRα and ABCA1 inhibited retinal inflammatory response, microglial response and preserved retinal function. TO901317 suppressed the NLRP3 inflammasome and the NF-κB signaling induced by Aβ1-40. Abstract: Amyloid β (Aβ) is a pathogenic peptide associated with many neurodegenerative diseases such as Alzheimer's disease and Parkinson's disease. The retinal inflammation in response to Aβ is implicated in the pathogenesis of several ocular diseases including age-related macular degeneration, Alzheimer's-related optic neuropathy and glaucoma. In the present study, we found that a single intravitreal injection of oligomeric Aβ1-40 in mouse activated the NLRP3 inflammasome and the NF-κB signaling, induced the production of inflammatory cytokines including TNF-α and IL-6. In addition, Aβ1-40 caused retinal function impairment while no noticeable morphological changes were observed under light microscope. Furthermore, immunohistochemical results showed that Aβ1-40 enhanced the number of Iba1-positive cells in the inner retina. The mRNA expressions of LXRα and LXRβ decreased in the neuroretina of the Aβ1-40-injected mice. No significant difference was found on the protein expressions of LXRs and ABCA1 in both neuroretina and RPE/choroid complex between the Aβ1-40-injected group and the control group. A synthetic LXR ligand, TO901317 (TO90), enhanced the expressions of LXRα and ABCA1 at both mRNA and protein levels in the Aβ1-40-injected mice, while the LXRβ expression was unchanged. TO90 preserved ERG a- and b-wave amplitudes and reduced the number of Iba1-positive cells in the Aβ1-40-treated retina. Furthermore, TO90 down-regulated the mRNA levels of TNF-α and IL-6, as well as the expressions of p-IκBα, NLRP3, caspase-1 and IL-1β in the Aβ1-40-injected animals. We suggest that activation of LXRα and its target gene ABCA1 exerts potent anti-inflammatory effect on the Aβ-treated retina.